Effect of different deficit irrigation regimes on vine performance, grape composition and wine quality of the “Primitivo” variety under mediterranean conditions - P. Losciale; L. Conti; S. Seripierri; V. Alba; F. Mazzone; L. Rustioni; G. di Leo; F. Tarricone; L. Tarricone (Irrigation Science, 2024)
Climate change represents one of the current major challenges and the improper use of water resources is an impeding threat. Agricultural research can play a crucial role by developing innovative strategies and techniques to reduce water use without affecting crop productivity and quality, particularly in grapevine growing in Mediterranean areas, as both productivity and wine quality are quintessential for the economic and ecologic sustainability of this crop. The present study aimed to define a deficit irrigation strategy for the “Primitivo” grapevine cultivar, taking into account the overall pathway of the vineyard performance in terms of leaf functionality, starch reserves, vine productivity, and wine quality. The trial was carried out in Southern-Italy on a three year-old, drip irrigated vineyard, imposing four deficit irrigation regimes for two consecutive seasons, consisting of 29 (T29), 55 (T55), 85 (T85) and 100% (T100) of crop evapotranspiration (ET C ). Mild water restriction (T85) did not affect vegetative nor reproductive vine performance. Deficit irrigation at 55% ET C lowered leaf functionality, starch accumulation, vine vigour and yield, due to a reduction of cluster weight; however, wine acidity and phenolic compounds were increased. T29 further decreased yield, as also the number of clusters was reduced. The most water-stressed treatment revealed a low concentration of malic acid in the must and a consequent increase of the ethanol sensation in the wine. After 9 months ageing, T85 had the highest wine colour intensity suggesting this treatment as the most promising in terms of quality and quantity of wine as well as for water saving.